Stigma terhadap Gangguan Jiwa dan Kaitannya dengan Praktik Seksisme dalam Budaya Paternalistik Bali - Inke Kusumastuti; Cokorda Bagus Jaya Lesmana (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Stigma toward mental illness is a complex construct incorporating personal, social, and structural. One of the social components that might significantly comprise stigma is the cultural aspect. Asian culture, generally, and Balinese culture, especially, is heavily embedded with the practice of paternalism which is a part of sexism. The practice of sexism as one form of discrimination might imply a high tendency to stigmatize people with mental illness. Therefore, it would be relevant to discuss the possible correlation between stigma and mental illness within the context of the predominant sexism-loaded paternalistic culture in Bali. This literature review covers several subtopics, including stigma and discrimination, sexism and its correlation with mental illness, and cultural aspects that might influence stigma concluded with recommendations for culturally sensitive mental health practice.